2016
DOI: 10.1097/md.0000000000005682
|View full text |Cite
|
Sign up to set email alerts
|

Delayed treatment of septic arthritis in the neonate

Abstract: There is still controversy on the management of septic arthritis in neonates. This study aims to investigate the treatment of septic arthritis in neonates.We reviewed 52 neonates (37 males and 15 females) with septic arthritis in our hospital during 2004 to 2015. The mean age at onset of infection was 17.5 ± 7.6 days, mean age at admission was 32.6 ± 10.7 days. A total of 56 joints were involved (22 knees, 18 shoulders, 13 hips, and 3 other joints). Thiryt-six patients underwent surgical drainage, 14 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…The review of Li et al 7 of 52 cases with septic arthritis in the neonate revealed a percentage of appearance of 32.1% regarding the shoulder, with pseudopalsy as the earliest sign in 50% cases. In their study, children that fulfilled three criteria out of five were diagnosed with septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The review of Li et al 7 of 52 cases with septic arthritis in the neonate revealed a percentage of appearance of 32.1% regarding the shoulder, with pseudopalsy as the earliest sign in 50% cases. In their study, children that fulfilled three criteria out of five were diagnosed with septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The main results of these six studies are presented in Table . Other past publications on this topic have focused on newborn infants or premature infants or presented case studies .…”
Section: Discussionmentioning
confidence: 99%
“…17,22,26 However, studies conducted by Haeffs et al and Li et al did not observe statistical significant between surgical management and treatment outcomes. 6,27 Patients from the rural areas had a good treatment outcome compared to those who came from the urban areas. This might be due to the fact that patients from the urban areas had more comorbid conditions (diabetes and HIV/AIDS) compared to those from the rural areas and more patients from the rural areas received surgical interventions compared to those from the urban areas.…”
Section: Discussionmentioning
confidence: 99%